Facebook and twitter for seniors for dummies ebook - Collier, Marsha (Dummies., 2010)
A fun and easy social media guide for the over-55 set People over 55 were the fastest-growing user group on Facebook in the first half of 2009, and they're flocking to Twitter at a faster rate than their under-20 grandchildren. From basic information about establishing an Internet connection to rediscovering old friends, sharing messages and photos, and keeping in touch instantly with Twitter, this book by online expert Marsha Collier helps seniors jump right into social media. Seniors are recognizing the communication possibilities of Facebook and Twitter and are signing up in record numbers This plain-English guide explains how to get online, set up a Facebook profile, locate friends, post public and private messages, share photos, create events, follow local businesses and friends on Twitter, create a blog, play games, and more Marsha Collier explains every step with the same friendly, comfortable style that has made her eBay For Dummies books bestsellers Facebook & Twitter For Seniors For Dummies supplies everything seniors need to function confidently on these two social media platforms. The EPUB format of this title may not be compatible for use on all handheld devices.